Life in biophotovoltaics systems - Ge-Zhang, Shangjie; Cai, Taoyang; Song, Mingbo (Frontiers in Plant Science, 2023)
As the most suitable potential clean energy power generation technology, biophotovoltaics (BPVs) not only inherits the inherent advantages of traditional photovoltaics, but also solves the disadvantages of high pollution and high energy consumption in the manufacturing process, providing new functions of self-repair and natural degradation. However, BPV has the disadvantage of low photocurrent output. The basic idea of BPV is to collect light energy and generate electric energy by using photosynthetic autotrophs or their parts, and the core is how these biological materials can quickly and low-loss transfer electrons to the anode through mediators after absorbing light energy and generating electrons. In this mini-review, we summarized the biological materials widely used in BPV at present, mainly cyanobacteria, green algae, biological combinations and isolated products, pointed out the limitations that affected the development of BPVs’ biological materials, and put forward reasonable assumptions accordingly.